2023
DOI: 10.22175/mmb.15705
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Acerola Cherry Powder in Combination With Rosemary Extract Extends the Shelf Life of Beef Chuck Roll and Bone-In Short Rib Steaks

Jessie B. Van Buren,
Brianna J. Buseman,
Tanya M. Weber
et al.

Abstract: Improving the shelf life of steaks from beef chuck rolls and bone-in short ribs, items commonly exported, will increase the demand of beef in international markets. Our objectives were to determine the effect of topically applying combinations of acerola cherry powder and rosemary extract on steak color and lipid oxidation of beef chuck roll and bone-in short rib. USDA Choice beef chuck rolls (Institutional Meat Purchase Specifications [IMPS] 116A; N=9) andbone-in short ribs (IMPS 123A; N=18) were aged (0°C) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Unfortunately, limited research has been conducted using antioxidants on beef following frozen storage and thawing. As previously stated, Van Buren et al [14,15] found that acerola cherry powder and rosemary extract improve the shelf life of fresh beef. The present study aims to evaluate the effects of these antioxidants on previously frozen beef.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Unfortunately, limited research has been conducted using antioxidants on beef following frozen storage and thawing. As previously stated, Van Buren et al [14,15] found that acerola cherry powder and rosemary extract improve the shelf life of fresh beef. The present study aims to evaluate the effects of these antioxidants on previously frozen beef.…”
Section: Introductionmentioning
confidence: 82%
“…Interestingly, the control bone marrow had a sharp decline in redness (a*) from day 0 to day 1, whereas all antioxidant-treated bone marrow samples had a delayed or more gradual decline in redness, and all antioxidant-treated bone marrow samples were redder than the control on day 1. Previous research had shown that antioxidants were effective in improving the bone marrow color by delaying hemoglobin oxidation and myoglobin oxidation similarly [2,14,15,28,29]. Bone marrow samples treated with R, M3, and M4 were also, on average, redder than the control on days 2 and 3.…”
Section: Retail Objective Colormentioning
confidence: 88%
See 1 more Smart Citation